PERAN BUDAYA USAHA TANI TERNAK SAPI POTONG DALAM KEHIDUPAN EKONOMI PETANI DESA (STUDI KASUS DI DESA MURAHARJO KECAMATAN KUNDURAN KABUPATEN BLORA) - Purwanto, Wahyu (Solidarity: Journal of Education, Society and Culture, 2013)
Village Community Muraharjo still very strong with the local culture or tradition, even affecting the way they meet the needs of life, farming, and animal husbandry. Muraharjo society in raising beef cattle are also affected also influenced their culture, it is manifested in the way of raising beef cattle farming as a way to follow their parents or previous generations. The purpose of this study was to answer the problem: (1) How does the culture of the cattle farmers in the Village District Muraharjo Kunduran Blora district. (2) What is the role of culture in the management of cattle farming in the Village District Muraharjo Kunduran Blora district. Conclusions from this research is the effort yani cattle in the village has not been maximized Muraharjo well for the welfare of the community because of the pattern of traditional businesses still are not looking for economic benefits but rather to mampertahankan existing traditions and inherited from their predecessors. Tingkt low education and lack of knowledge possessed by their menjadika livestock farmers tend mempelakukan all the cows at their disposal to assist the activities in the field no matter ordinary cows or beef cattle. In accordance with the theory subtantifis dati Polanyi, keiatan economy will develop in accordance with the culture stempat .. Economic phenomenon that is in the process of msayarakat Muraharjo previous symptoms and symptoms that occur in the present will affect the symptoms that will occur in the future